Computational materials science : from Ab Initio to Monte Carlo methods /: from Ab Initio to Monte Carlo methods. (2018) - Ohno, K (Kaoru), 1955-; Esfarjani, K (Keivan), 1964-; Kawazoe, Y (Yoshiyuki), 1947-
No abstract available